The Development of a Web Profile System for SMK N 1 Singingi Hilir Using the Prototyping Method - Sucinta, Hanny Handayani; Mahmuda, Muhimmatul; Mujahidah, Latifatul; Sugiantoro, Bambang (IJISTECH (International Journal of Information System and Technology), 2025)
The development of a web-based information system for the school profile is a strategic step in improving the accessibility of information and interaction between the school and the community, particularly prospective students and parents. This study aims to develop a web profile system for SMK N 1 Singingi Hilir by applying the Prototyping method, so that the system can be developed based on user feedback during the design process. This system presents comprehensive information about the school profile, expertise programs, facilities, student activities, and other important information. With the Prototyping approach, system development is carried out iteratively by building an initial prototype, which is then improved based on user evaluations. The result of this development is expected to enhance school promotion as well as transparency and efficiency in delivering information.